Mental Health in Postoperative Thyroid Patients During the COVID-19 Pandemic - Yang, Shijie; Xu, Xiequn (Frontiers in Endocrinology, 2022)
Background: Little is known about mental health in patients after thyroid surgery during the peak of the COVID-19 pandemic in China. This study aimed to assess the mental health of postoperative thyroid patients and to explore potential factors associated with psychological symptoms. Methods: In this study, we surveyed 241 patients who underwent thyroid surgery at Peking Union Medical College Hospital. Insomnia, anxiety, depression, and posttraumatic stress symptoms (PTSS) were measured using the Insomnia Severity Index (ISI), Generalized Anxiety Disorder Questionnaire (GAD-7), Patient Health Questionnaire (PHQ-9), and Impact of Event Scale-Revised (IES-R), respectively. Results: A significant proportion of postoperative patients reported experiencing insomnia, anxiety, depression, and PTSS. Patients that were older, single/divorced/widowed, and less educated; had lower income and poor general health; had undergone surgery within the past six months; had disrupted follow-up, and; searched social media for COVID-19-related information were associated with worse mental health. Conclusions: During the COVID-19 pandemic, postoperative thyroid patients tended to develop mental health problems and have less psychological support, emphasizing the importance of patient education and psychological interventions.